Pengaruh Modal, Tenaga Kerja, Jam Kerja dan Promosi Terhadap Pendapatan Kedai Kopi di Kelurahan Kertak Baru Ulu - Mulyani, Nida; Rizali, Rizali (PPJP ULM, 2024)
The purpose of this thesis research is to analyze the factors that can affect the income of coffee shops in Kertak Baru Ulu Village. The research location is in Kertak Baru Ulu Village, Banjarmasin with a total population and sample of 15 coffee shops. Using quantitative regression analysis techniques. Research data comes from primary data conducted through interviews and questionnaires. Variables consist of income, capital, number of workers, working hours and promotions. The study was conducted using multiple regression analysis (OLS) with a significance level of 0.05. The results in this study prove that the factors of capital, number of workers, working hours and promotions simultaneously have a significant effect on the income of the coffee shop in Kertak Baru Ulu Village. Capital factors and the number of workers partially affect the income of coffee shops. The effect of capital, number of workers, working hours and promotions on coffee shop income by 95% and 5% is explained by other factors.